2022
DOI: 10.1615/jflowvisimageproc.2022041197
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Lagrangian-Based Particle Tracing Using Deep Learning

Abstract: Time-varying vector fields produced by computational fluid dynamics simulations are often prohibitively large and pose challenges for accurate interactive analysis and exploration. To address these challenges, reduced Lagrangian representations have been increasingly researched as a means to improve scientific time-varying vector field exploration capabilities. This paper presents a novel deep neural network based particle tracing method to explore time-varying vector fields represented by Lagrangian flow maps… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…More recently, Han et al [HSJ22] used precomputed particle trajectories to train a deep learning model and replace interpolation with an inference process to derive new particle trajectories in unsteady flow. Once trained, the model has a reduced memory footprint and can be used to infer several locations along thousands of pathlines in a few seconds using a GPU.…”
Section: Algorithmic Optimizationsmentioning
confidence: 99%
“…More recently, Han et al [HSJ22] used precomputed particle trajectories to train a deep learning model and replace interpolation with an inference process to derive new particle trajectories in unsteady flow. Once trained, the model has a reduced memory footprint and can be used to infer several locations along thousands of pathlines in a few seconds using a GPU.…”
Section: Algorithmic Optimizationsmentioning
confidence: 99%
“…Uncertainties can be introduced in different stages of visualization pipeline, including data acquisition [5,7,30,31,36], data transformation [9,19,34], visual mapping and rendering [6,11,12,26,28,33] stages. In deep learning for scientific visualization, Han et al [17] found that the model's performance is affected by flow behavior. Regions with greater separation in the flow field have higher errors.…”
Section: Related Workmentioning
confidence: 99%
“…These mechanisms include Brownian motion associated with chaotic, random vibrations of particles, the force of gravity, and collisions between the aerosol particles themselves. A mathematical model of aerosol movement based on the particle tracing method is presented below [27]:…”
Section: Investigation Of Approachesmentioning
confidence: 99%